Pengaruh Kualitas Pelayanan Dan Kualitas Produk Terhadap Kepuasan Pelanggan Coffee Shop PT Jagat Pramudita Aksata: The Influence of Service Quality and Product Quality on Customer Satisfaction of PT Jagat Pramudita Aksata Coffee Shop - Hafiz, Abdul; Hastasari, Ratih; Saputra, Wawan (CV Warnak Johanna Nusantara, 2026)
Abstracts - The Coffeee shop industry in Indonesia has seen rapid growth in recent years, driven by changing urban lifestyles, especially among millennials and Gen Z. Coffeee shops are no longer just places to enjoy beverages but have become social and productive spaces. PT. Jagat Pramudita Aksata, originally operating in earphone distribution, has expanded into the F&B sector by launching the Coffeee shop “JOY Listening Space”. In an increasingly competitive market, the company must pay close attention to product and service quality as key drivers of customer satisfaction. This study aims to examine the effect of Service Quality and Product Quality on Customer Satisfaction. A quantitative approach was employed using a non-probability sampling technique with 100 respondents. Data were analyzed using validity and reliability tests, multiple linear regression, t-test, and F-test. The results show that Service Quality does not have a significant partial effect on Customer Satisfaction (t-value 0.754 < t-tabel 1.661), while Product Quality does (t-value 3.174 > t-tabel 1.661). Simultaneously, both variables significantly influence Customer Satisfaction (F-value 9.157 > F-tabel 2.70, sig. 0.001 < 0.005). These findings emphasize the importance of enhancing both product and service quality to retain customer loyalty.